Phase III, randomised trial of avelumab versus physician's choice of chemotherapy as third-line treatment of patients with advanced gastric or gastro-oesophageal junction cancer: primary analysis of JAVELIN Gastric 300. (24th July 2018) - Bang, Y -J; Ruiz, E Yañez; Van Cutsem, E; Lee, K -W; Wyrwicz, L; Schenker, M; Alsina, M; Ryu, M -H; Chung, H -C; Evesque, L; Al-Batran, S -E; Park, S H; et al.
Abstract: Background: There currently are no internationally recognised treatment guidelines for patients with advanced gastric cancer/gastro-oesophageal junction cancer (GC/GEJC) in whom two prior lines of therapy have failed. The randomised, phase III JAVELIN Gastric 300 trial compared avelumab versus physician's choice of chemotherapy as third-line therapy in patients with advanced GC/GEJC. Patients and methods: Patients with unresectable, recurrent, locally advanced, or metastatic GC/GEJC were recruited at 147 sites globally. All patients were randomised to receive either avelumab 10 mg/kg by intravenous infusion every 2 weeks or physician's choice of chemotherapy (paclitaxel 80 mg/m 2 on days 1, 8, and 15 or irinotecan 150 mg/m 2 on days 1 and 15, each of a 4-week treatment cycle); patients ineligible for chemotherapy received best supportive care. The primary end point was overall survival (OS). Secondary end points included progression-free survival (PFS), objective response rate (ORR), and safety. Results: A total of 371 patients were randomised. The trial did not meet its primary end point of improving OS {median, 4.6 versus 5.0 months; hazard ratio (HR)=1.1 [95% confidence interval (CI) 0.9–1.4]; P  =   0.81} or the secondary end points of PFS [median, 1.4 versus 2.7 months; HR=1.73 (95% CI 1.4–2.2); P  >   0.99] or ORR (2.2% versus 4.3%) in the avelumab versus chemotherapy arms, respectively. Treatment-related adverse events (TRAEs) of any grade occurred in 90 patients (48.9%) and 131 patients (74.0%) in the avelumab and chemotherapy arms, respectively. Grade ≥3 TRAEs occurred in 17 patients (9.2%) in the avelumab arm and in 56 patients (31.6%) in the chemotherapy arm. Conclusions: Treatment of patients with GC/GEJC with single-agent avelumab in the third-line setting did not result in an improvement in OS or PFS compared with chemotherapy. Avelumab showed a more manageable safety profile than chemotherapy. Trial registration: ClinicalTrials.gov: NCT02625623.